2000
DOI: 10.1007/s11745-000-0595-x
|View full text |Cite
|
Sign up to set email alerts
|

n−3 Fatty acid deficiency decreases phosphatidylserine accumulation selectively in neuronal tissues

Abstract: We have previously shown that the docosahexaenoate (22:6n-3) status in membrane phospholipids influences the biosynthesis and accumulation of phosphatidylserine (PS) in brain microsomes and C6 glioma cells. In the present study, we investigated whether the observed effect of membrane docosahexaenoic acid status on PS accumulation is universal or occurs specifically in neuronal tissues. We observed that rat brain cortex, brain mitochondria, and olfactory bulb, where 22:6n-3 is highly concentrated, contain signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
108
0
8

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 120 publications
(125 citation statements)
references
References 51 publications
9
108
0
8
Order By: Relevance
“…Similarly, DHA supplementation in cultured glia or neuronal cells has been shown to increase PS content (20,21). In contrast, depletion of DHA under n-3 fatty acid deficiency led to a reduced PS level in neuronal tissues, including rat brain cortex, hippocampus, pineal, and olfactory system (22)(23)(24), despite the compensatory replacement of DHA with DPA. Consistently, DHA containing phospholipids were found to be the preferred substrate to DPA species for PS biosynthesis (25).…”
mentioning
confidence: 99%
“…Similarly, DHA supplementation in cultured glia or neuronal cells has been shown to increase PS content (20,21). In contrast, depletion of DHA under n-3 fatty acid deficiency led to a reduced PS level in neuronal tissues, including rat brain cortex, hippocampus, pineal, and olfactory system (22)(23)(24), despite the compensatory replacement of DHA with DPA. Consistently, DHA containing phospholipids were found to be the preferred substrate to DPA species for PS biosynthesis (25).…”
mentioning
confidence: 99%
“…In neuronal membranes, DHA is highly enriched in aminophospholipids, especially PS (1,2,4,5-10,114). We and others have previously demonstrated that the enrichment of DHA in cell membranes increases PS synthesis and, conversely, that depletion of this fatty acid by an n-3-deficient diet or by chronic ethanol exposure decreases the accumulation of PS (115)(116)(117)(118). Considering the fact that PS is the major negatively charged phospholipid class in many mammalian cell membranes and many of the signaling proteins such as protein kinases are influenced by PS (119-121), this alteration of PS content may have significant implications for cellular function.…”
Section: Antiapoptotic Effect Of Docosahexaenoic Acidmentioning
confidence: 87%
“…Astrocytes, but not neurons, make 22:6n-3, thus providing a potential source of 22:6n-3 to activate RXR␣ (15). Second, n-3 PUFA deficiency is correlated with a decline in PS and increased neuronal apoptosis (11,30,31). Neuronal apoptosis is linked to Raf-1 and plasma membrane PS content.…”
Section: N-3 Pufa Effects On Membrane Structure and Function N-3 Pufamentioning
confidence: 99%